Persis Solo Anti Disturbance Stadium - Rasyid, Ridho, MS. Priyono Nugroho, ST.MT, Ir. Samsudin Raidi, MSc (2016)
Football is the sport become a magnet thousands of spectators, then indirectly will form a community or organization that aims to support the fans their pride clubs each. We know that groups of hardline supporters will always do things beyond human reasoning extreme just to kepetingan or the glory of the club are supported. Analysis approach and concept planning and design of Persis Solo Disturbance Stadium include Site Location Analysis, Achievement, View, Noise, Climatology orientation, Landscape, Mass, Space, Interior Exterior view, Utility Structures and Architectural Emphasis expected as a design reference mendesaian. The results of the architectural emphasis is to design a stadium that berstandart according to FIFA requirements with an emphasis stadium riot. With the concept can prevent violence both inside and outside the stadium. Three concepts were implemented, namely the separation area anatar stands, screning area as spectators filter, and the barrier stands between the stands and the stands to the field.' Keywords: stadium, riots